Corporate insolvency : the protection of creditors interests / Mohammad Rizal Salim - Salim, Mohammad Rizal (2001)
The principle of separate legal personality is an established doctrine in company law, which was codified by the legislature and further refined and enforced by the courts. The primary purpose for this doctrine is to encourage entrepreneurship, by shifting the risks of business failure away from entrepreneurs and businessmen to creditors and other risk bearers. Since creditors stand to risk business failure, they will naturally try to minimize these risks, principally through contract. This, however, is not enough, especially when business failure was caused by unfair or improper conduct of these entrepreneurs and other corporate controllers. This is where the courts play an important role, by providing exceptions to the separate legal personality rule, commonly known as lifting or piercing of the corporate veil, to curb unfair or improper conduct by corporate controllers. However, over-reliance on the role of the courts to curb unfair or improper conduct is not desirable. Judges make laws only when a dispute is litigated upon; and its development will often be disjointed and lacking in coherence. This is why the legislature plays an important role to protect creditors against unfair and improper conduct by corporate controllers which prejudices creditors of the company. This research paper seeks to examine certain laws which directly affects, or attempts to protect, creditors from unfair and improper conduct by corporate controllers.